Educational Thought in Nahdlatul Ulama and Muhammadiyah: The Perspectives of Islam Nusantara and Progressive Islam - Andi Bangsawan Tolere; Andi Jufri; Andi Aderus (Yayasan Rahmat Islamiyah, 2026)
This study analyzes and compares the educational thought of Indonesia’s two largest Islamic organizations, Nahdlatul Ulama (NU) and Muhammadiyah, through the respective analytical frameworks of Islam Nusantara (Nusantara Islam) and Islam Berkemajuan (Progressive Islam). The objective of this research is to unpack the philosophical foundations, pedagogical characteristics, and contemporary contributions of both movements in responding to the demands of modernity and national identity. Utilizing a qualitative, library-based research design with a comparative-hermeneutic approach, this study examines foundational literature, institutional documents, and key intellectual works from both organizations. The findings reveal that NU’s educational thought, anchored in Islam Nusantara, emphasizes cultural acculturation, the preservation of the traditional pesantren system, local wisdom, and contextual jurisprudence (fikh). Conversely, Muhammadiyah’s educational model, driven by Progressive Islam, prioritizes modernization, religious purification combined with reform (tajdid), the integration of secular and religious sciences, and structured institutional efficiency. Despite their methodological divergences—NU relying on traditional continuity and cultural flexibility, and Muhammadiyah focusing on institutional reform and rational modernization—both organizations operate synergistically to counter extremism, reinforce religious moderation (wasathiyah), and foster human resources capable of thriving in a globalized world.